Development of a sensor for corona current measurement under high-voltage direct-current transmission lines. (August 2016) - Xin, Encheng; Yuan, Haiwen
A sensor-based distributed measurement system is designed for collecting and monitoring the corona current under the extremely high-voltage direct-current transmission lines. It is highly significant for researching the corona characteristics of extremely high-voltage direct-current transmission lines to reduce the corona effect, operating loss, and environmental impact. A new shared memory strategy has been studied based on field-programmable gate array and ARM. Based on field-programmable gate array technology, the fiber-optic transmission scheme for wide-frequency corona current high-speed signal has been set up to ensure the safety and the reliability of corona current measurement system. The proposed system has been used in China's state grid high-voltage direct-current test base and the in situ power transmission projects. Based on the experimental results, the proposed measurement system demonstrates that it can adapt to the complex electromagnetic environment under the transmission lines and can accomplish the accurate, flexible, and stable demands of the electric-field measurement.